2010
DOI: 10.1097/mlr.0b013e3181ca3ecb
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access and the Use of Screening Mammography

Abstract: Background Screening mammography rates vary geographically and have recently declined. Inadequate mammography resources in some areas may impair access to this technology. We assessed the relationship between availability of mammography machines and the use of screening. Methods The location and number of all mammography machines in the US were identified from US Food and Drug Administration records of certified facilities. Inadequate capacity was defined as <1.2 mammography machines per 10,000 women aged 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
99
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 36 publications
6
99
0
2
Order By: Relevance
“…Similar to an earlier examination of national mammography capacity, our findings indicate that capacity is not distributed equally across counties [18] and that 870 (27.7 %) counties have zero capacity. Although the number of mammography facilities and machines decreased slightly between 2003 and 2009, the percentage of zerocapacity counties remained fairly consistent.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to an earlier examination of national mammography capacity, our findings indicate that capacity is not distributed equally across counties [18] and that 870 (27.7 %) counties have zero capacity. Although the number of mammography facilities and machines decreased slightly between 2003 and 2009, the percentage of zerocapacity counties remained fairly consistent.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies comparing screening prevalence to availability of mammography facilities using data from the Behavioral Risk Factor Surveillance System (BRFSS) found that unavailability of mammography facilities may be a barrier to screening [18,36]. We could not provide a direct assessment of the relationship between screening utilization as reported in the BRFSS and the availability of screening facilities from the FDA because of BRFSS data limitations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The goal of an organized mammography screening program is to offer high level medical care to every woman at a reasonable expense. Previous studies have shown barriers to entry into the health system for low income women and women in an area with inadequate mammography capacity, resulting in delays in diagnosis (Elkin et al, 2010;Maly et al, 2011). Providing mobile mammography services with community organizations, can be effective in increasing access and decreasing barriers to screening hard-to-reach populations.…”
Section: Discussionmentioning
confidence: 99%
“…14 Importantly, residents in communities with a lower mammography capacity have lower rates of screening mammograms. 15 Whether similar population-level factors impact riskbased screening uptake and medical care among childhood cancer survivors is not known. Thus, this study was designed to evaluate the role of population-level socioeconomic and health system factors on childhood cancer survivors' riskbased medical care and screening practices, independent of individual-level factors.…”
Section: Introductionmentioning
confidence: 99%